Functional ceramics through mechanochemical activation - Kong, Ling Bing (IOP ebooks. 2020 collection., 2020)
This book offers an overview of the progress in the synthesis of powders and fabrication of ceramics of selected materials created using mechanochemical activation. It covers ferroelectric materials, ferrite ceramics with magneto-dielectric properties, mullite ceramics with controllable microstructure and anisotropic grain growth behaviours. The book is a valuable reference for advanced students, researchers and engineers, in materials science and engineering, applied physics, solid-state lasers and solid-state physics.